"The role and effectiveness of national and international alternative means in dispute resolution". Study compared to Islamic law. - Al Naabi, Sultan Khamis Issa; Emam, Maher Ibrahim Ebed; Fakhry, Wael Mahmoud (Journal of Ecohumanism, 2025)
The research aims at defining alternative means, what they are and what they are important for dispute resolution, highlighting the role of alternative means in the resolution of domestic and international disputes, revealing the effectiveness of such means in resolving disputes, resolving litigations, and indicating the legal procedures for resorting to such alternative means at the domestic and international levels, while indicating the legal safeguards offered by such alternative means to disputes.To complete the study, the researchers followed a descriptive, analytical and comparative approach.The study’s importance was to identify the nature of these alternative means, the procedures that could be used to resolve disputes beyond the scope of the traditional court, and to highlight their role at the domestic and international levels.The researchers concluded that alternative means called friendly or diplomatic means were capable of absorbing and addressing many domestic and international issues diplomatically and judicially through the conventional judiciary, if it has the necessary legal legislation to make it more effective and capable of absorbing and resolving cases amicably in Oman and in other countries.The researchers recommended that disputes could be resolved by peaceful means; away from judicial courts, if the parties’ will exists, and appropriate procedures are in place to resolve them.The researchers appeal to all legislators to seek the establishment of diplomatic courts to resolve local disputes amicably, as adopted by the Sultanate of Oman and the Maghreb, to give judgement to the judgement rendered by those courts, and to make them judgmental in force in accordance with the judgements rendered by the arbitral tribunal and centres and the International Court of Justice.